Modeling the Exposure of the Macaronesia Islands (NE Atlantic) to Marine Plastic Pollution - Cardoso, Cláudio; Caldeira, Rui M. A. (Frontiers in Marine Science, 2021)
The constant increase of marine plastic pollution poses an unprecedented risk to oceanic islands, which become increasingly exposed to a hazard of which they have very little control. Located in the Northeast Atlantic Ocean, the Macaronesia is comprised by the Azores, Madeira, Canary Islands, and Cabo Verde. Although past studies suggest that most plastic items collected on these islands are from offshore regions, their actual sources remain unclear to present date. As such, we focus on the characterization of the potential sources and pathways of plastic particles reaching the Macaronesia archipelagos. This is achieved by combining modeled datasets for ocean currents, winds and waves with a Lagrangian tool used to track virtual particles released around the archipelagos for a 10-year period, making a distinction between surface and submerged particles. Global drifter trajectories are also assessed, selecting those that intercept the archipelagos. Our results demonstrate that the North Atlantic subtropical gyre is the most conspicuous feature in particles and drifter trajectories. The Gulf Stream acts as the main pathway for all archipelagos at a regional scale, though with less significance to Cabo Verde. Surface particles are connected to regional sources in a shorter timescale than mixed particles, mainly because of the wind. Intercepting high-windage particle trajectories are dominant at the center of the North Atlantic subtropical gyre, demonstrating that particles originating from the North Atlantic “garbage patch” are most likely to intercept the archipelagos if considerably exposed to the wind. Regarding the connectivity to sources, all archipelagos are significantly exposed to areas of intensive fishing activity, mainly those located in the Gulf Stream (Azores), in international waters off the Portuguese coast (Madeira and Canary Islands) and along the Northwestern African coast (Cabo Verde). The east coasts of Central and North America are the main sources of land-based particles reaching the Azores, Madeira, and Canary Islands, whereas the Northwestern African coast is the main source for land-based particles reaching Cabo Verde. Our results demonstrate how vulnerable the Macaronesian archipelagos are to marine plastic pollution, highlighting the urgency for international cooperation to mitigate the exposure of oceanic islands to marine plastic pollution.